RETRACTED: Pemanfaatan Film Animasi Dengue Hemorrhagic Fever Selama Masa Pandemi Covid-19 - Muhammad Al-Irsyad; Septa Katmawanti; Farah Paramita; Rosuzeita Fauzi; Dea Aflah Samah; Gladys Cyntya Mahardyka; Purnama Devita Sari; Belisa Fitria Az Zahra Bachtiar (Universitas Negeri Malang, 2022)
Following a rigorous, carefully concerns and considered review of the article published in Preventia: The Indonesian Journal of Public Health to article entitle “Pemanfaatan Film Animasi Dengue Hemorrhagic Fever Selama Masa Pandemi Covid-19” Vol. 7, No. 1 (2022), DOI: http://dx.doi.org/10.17977/um044v7i12022p48-58This paper has been found to be in violation of the Preventia: The Indonesian Journal of Public Health publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Jurnal Kesehatan Lingkungan, Vol. 19, No. 2 (2022), DOI: https://doi.org/10.31964/jkl.v19i2.475The document and its content has been removed from Preventia: The Indonesian Journal of Public Health and a reasonable effort should be made to remove all references to this article.